Development and Practice of Islamic Law Codification in Southeast Asia - Darna, Andi; Ridhwan, Ridhwan; Nurdin, Abidin; Nizar, Mohammad (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This article aims to examine the development of Islamic law codification in Southeast Asia. Southeast Asia is a region with Muslims who have peaceful, tolerant, and moderate characteristics. Islam that developed in Southeast Asia has differences with those in Arabia, Morocco, Turkey, India, Pakistan, Uzbekistan, and China in terms of culture and customs. The main question that will be answered in this article is how the codification of Islamic law developed in Southeast Asia. The study uses empirical legal juridical studies with an approach to the social history of Islamic law. The article concludes that from the perspective of Islamic legal history, the development of legal codification has experienced three phases, namely: the kingdom, colonialism, and post-colonialism. Countries with a Muslim majority, such as Indonesia, Malaysia, and Brunei Darussalam, have experienced quite significant development, while countries such as Thailand, the Philippines, and Singapore have not experienced any significant development, and countries such as Cambodia, Vietnam, and Myanmar tend to have no development. In addition, Islamic law that developed in Southeast Asia accommodates local values ​​and customs that become a new identity or